Isolated chemohyperthermal perfusion of the liver with melphalan in the treatment of unresectable liver metastases with uveal melanoma - A. D. Kaprin; S. A. Ivanov; V. M. Unguryan; L. O. Petrov; E. A. Kruglov; Yu. A. Pobedintseva; E. V. Filimonov; A. G. Isaeva (Исследования и практика в медицине, 2021)
Uveal melanoma belongs to rare malignant neoplasms, and the biological peculiarity of this tumor determines the high rate of distant metastasis, which reaches 60 %. Most frequently, uveal melanoma metastases are localized in the liver and have an isolated character. At the same time, despite the achievements of modern drug therapy, the treatment results of this category of patients remain unsatisfactory. Among the regional methods of treatment of metastatic uveal melanoma, surgical treatment is considered to be the most effective. Median survival rate in the group of radically operated patients (R0) is 27 months. At present, in the vast majority of cases, surgical treatment is impossible because of multiple bilobar metastasis and advanced cancer process. Median life expectancy of patients with liver metastases is only 9 months. A promising method of regional treatment of inoperable metastatic uveal melanoma is isolated liver chemoperfusion. Multidisciplinary team of Radiology Scientific Research Center and Kostroma Oncologic Dispensary for the first time in Russia presents a clinical case of a patient with isolated inoperable uveal melanoma liver metastases using an innovative method - isolated high-dose chemo hyperthermic liver perfusion with melphalan. The article describes in detail the method of the procedure, estimates immediate (partial response in 1 month after the procedure) and long-term results of the method (stabilization of the condition against the background of immunotherapy in 9 months after surgery). Based on the presented clinical observation, isolated liver chemoperfusion with melphalan for this category of patients is reasonable. However, despite the encouraging immediate results, clinical experience needs to be accumulated in order to be further evaluated in clinical trials.